Ceruminous adenoma of the external auditory canal: 9 cases series with imaging and pathologic findings - Yang, Yifan; Liu, Honggang; Fang, Jugao; Li, Yongxin; Chen, Shubin (Frontiers in Oncology, 2023)
Objectives: Ceruminous adenoma is a rare benign tumor of the external auditory canal. This study aimed to present the clinical characteristics, imaging findings, pathological results and the management outcomes of the ceruminous adenoma. Patients and Methods: Patients undergoing surgery for ceruminous adenoma of the external auditory canal between the years 2004 to 2018. All patients with ceruminous adenoma were analyzed for demographic, clinical, radiological features and pathologic findings. The outcomes of the management were also evaluated. Results: Nine patients with ceruminous adenoma were included in the study. Hearing loss was the most common complaint (5/9, 56%)，followed by otalgia (4/9, 44%), pruritus (4/9, 44%), and otorrhea (2/ 9, 22 %). The tumors originated mostly from the cartilaginous portion of the external auditory canal(8/9, 89%) and merely from the bony portion of the external auditory canal （1/9，11%）. Pathohistological study indicated that the ceruminous adenomas were divided into three types: the ceruminous gland adenoma (6/9, 67% ), the ceruminous pleomorphic adenoma （2/9， 22%） and the ceruminous syringocystadenoma papilliferum（1/9,11%）. No recurrence was found during follow-up for two to fifteen years after surgical resection. Conclusion Ceruminous adenomas are rare entities. They originate mainly from the cartilaginous portion of the EAC, but occasionally from the bony portion of the EAC. The surgical section with enough margin is adequate for management of these tumors.